P008 Store-operated calcium entry controls immune cell function and activation in Inflammatory Bowel Disease. (27th May 2021) - Letizia, M; Kaufmann, U; Gerbeth, L; Sand, A; Brunkhorst, M; Wang, Y; Böttcher, C; Schlickeiser, S; Fernández-Zapata, M C; Kunkel, D; Siegmund, B; Feske, S; et al.
Abstract: Background: Inflammatory bowel disease (IBD) comprises ulcerative colitis (UC) and Crohn's disease (CD), both representing major clinical challenges in need of new treatment modalities to improve patient care. Store-operated calcium entry (SOCE) is the predominant calcium influx pathway in immune cells regulating many of their functional properties. Conditional knockout mice, in which SOCE signaling components are deleted in T cells, have revealed that SOCE is required for the induction of intestinal inflammation in mouse models of colitis. However, it is currently unknown whether the pharmacologic inhibition of SOCE is a suitable drug target in IBD and it remains elusive, which immune cell subsets are affected by the pharmaceutical blockade of SOCE. Therefore, we here aimed to investigate the effects of the SOCE inhibitor BTP-2 on the function and activation of lymphocytes isolated from IBD patients. Methods: PBMC and/or lamina propria lymphocytes (LPMC) were isolated from UC and CD patients undergoing colon resection. Cells were ex -vivo stimulated with PMA/Ionomycin in the presence or absence of increasing concentrations of BTP-2, fixed and stored at -80°C until acquisition by mass cytometry. LPMCs were stained using 37 lineage and functional markers targeting B, T, NK or myeloid cells and the resulting flow cytometry standard (FCS) files were analyzed by using cytobank and the R/Bioconductor 9 packages. Additionally, Ca2+ influx measurements were performed in order to assess the impact of SOCE inhibition on the calcium homeostasis of various immune cell subsets. Results: Data on B, T, NK, and myeloid cells revealed that treatment with BTP-2 causes a dose-dependent inhibition of calcium influx, demonstrating that BTP-2 is a potent inhibitor of SOCE in human LPMCs and PBMCs. By applying mass cytometry, we investigated how the gradual pharmacologic inhibition of SOCE affects the activation and pro-inflammatory functions of various immune cell subsets obtained from colon specimens of patients with UC and CD, which were characterized by the accumulation of CD4+ effector T cells, IFNγ-producing CD8+ T cells and IL-17-producing innate lymphoid cells (ILCs) compared to non-inflamed specimens. Remarkably, inhibition of SOCE attenuated the production of cytokines including IL-2, IL-4, IL-6, IL-17, TNF-α and IFNγ by T cells and ILCs, reduced the activation of B cells and decreased the production of IFNγ by myeloid cells without affecting the viability of primary human epithelial cells. Conclusion: Our data reveal for the first time that the cytokine production and the activation of several immune cell subtypes can be modulated by SOCE blockade in human intestinal inflammation, identifying SOCE as a novel therapeutic target in colitis.